Implementación y Validación de un Plan de Mantenimiento Existente para Inmuebles ICE - Ulate Vargas, Gustavo (Instituto Tecnológico de Costa Rica, 2012)
This document contains procedures used to implement and validate the Model Plan for Building Maintenance for Instituto Costarricense de Electricidad (ICE); which was designed by engineer. Pablo Camacho in 2009 but has not been developed or tested its operation The objective of this project is to test the proposed plan in a sample of two similar buildings in to ICE in the subarea Cartago, which contain customer service platforms, administrative offices and technical support. Are expected to implement and validate the tool, is emulated and applied to other buildings in the subarea of Cartago to go gradually developing it to the rest of the country. With this sample was determined that the evaluated method has a 90% efficiency for buildings ICE applicable as long as you follow the suggestions and steps provided in this project. Using historical data from inspections and corrective maintenance, be developed maintenance guidance applicable to each building, also be designed a system in Excel to the control in service quality. With this implementation can generate annual planning, avoiding interference with other projects and lower payroll costs, time and materials stored.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2012.
Keywords: Gestión del mantenimiento; Planificación; Flujograma; Validación; Métodos de muestreo